Constructing an evaluation index system for the tourism value of Guangdong's Maritime Silk Road cultural heritage - Mei, Wen-Bing; Li, Kun; Huang, Yi-Zhe (Frontiers in Sustainable Tourism, 2025)
Constructing an evaluation index system for the value of cultural heritage tourism resources can provide a scientific and practical basis for decision-making in both protecting Guangdong's Maritime Silk Road (MSR) cultural heritage and enhancing the effectiveness of its cultural tourism. Through a combination of literature review and grounded interviews, 28 evaluation factors were initially identified. Subsequently, using the Fuzzy Delphi Method and consulting expert panels drawn from government, industry, and academia, the list was refined and 26 key evaluation indicators were ultimately selected. The findings reveal that the value of MSR cultural heritage tourism resources in Guangdong can be categorized into four main dimensions: industrial service, historical remains, science education, and tourism and leisure. The levels of expert consensus on the importance of these dimensions were as follows: Industrial Service Value (7.37), Historical Heritage Value (7.21), Science and Education Value (7.00), and Tourism and Recreation Value (6.99). Among the individual indicators, the following six were considered of relatively high importance: Tourism Management Level (7.78), Historical and Cultural Significance (7.74), Maturity of Resource Infrastructure (7.58), Cultural Route Tourism (7.48), Local Community Participation (7.41), and Heritage Antiquity (7.40). In contrast, using MSR heritage tourism in Guangdong to experience exotic cultures or enhance popular religious beliefs did not receive wide academic recognition. The findings of this study offer a valuable reference for government authorities and industry stakeholders in developing strategies to enhance the impact and value of MSR cultural heritage tourism in Guangdong.